EFEKTIFITAS PELATIHAN DALAM PENINGKATAN PERAN KADER SEBAGAI PENDAMPING KELUARGA IBU HAMIL DI PUSKESMAS II SUMBANG - Arrum Firda Ayu Maqfiroch; Elviera Gamelia; Siti Masfiah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2018)
The number of maternal deaths in Banyumas Regency was ranked 4th out of 35 districts in Central Java by 2015. The mortality rate of mother in Banyumas District in 2014 is 114.73 per 100,000 live births. One of the dominant factors that affect the condition is the role of the family. The family of pregnant women is one of the potential groups in a society close to pregnant women and can become a health cadre partner. This study aimed to identify the effectiveness of training in increasing the role of cadres as a family counsellor of pregnant women in Puskesmas II Sumbang. This research used pre and post quasi experiment method with control design. The population in this study was cadres of pregnant women in the village in the area of ​​Puskesmas II Sumbang. The results of this study indicated that training was not effective in improving the role of cadres ( knowledge, attitude and communication skills of cadres) as a family counsellor of pregnant women. Keywords: Cadre, family counsellor of pregnant women, Sumbang